Reading the Sermon on the Mount : character formation and decision making in Matthew 5-7 - Talbert, Charles H. (Grand Rapids, Mich. : Baker Academic, 2006)
The Sermon on the Mount is one of the most familiar passages in the New Testament. In this concise and clearly-written introduction to and commentary on the Sermon, Charles Talbert pays particular attention to its role in character formation and ethical decision making. After introductory chapters on reading the Sermon on the Mount, the book offers a section-by-section commentary. Talbert points out structural highlights, provides illuminating cross-references to Jewish and Greco-Roman literature, and concludes each section with a consideration of how it contributes to character formation and how it can be used with the rest of Scripture for ethical decision-making. The book is packed with insights that will be of great use to students as well as those who preach and teach the Sermon.
Originally published: Columbia, S.C. : University of South Carolina Press, c2004.
Includes bibliographical references (p. [149]-160) and indexes.
Keywords: Sermon on the mount -- Criticism, interpretation, etc; Sermon on the mount; Criticism, interpretation, etc